The Effectiveness of Using Finger Print in the Environmental Office of Soppeng Regency - Haedar Akib; Indah Sari; Risma Niswaty (Journal of Social Science and Economics (JOSSE), 2024)
The use of finger print is an electronic-based attendance tool used to see the level of employee discipline. This study aims to determine the effectiveness of finger printing use in the Soppeng Regency Environmental Office. To achieve this goal, researchers use data collection techniques through observation, questionnaires, interviews, and documentation. This research is a quantitative descriptive research. The population in this study was all employees of the Soppeng Regency Environmental Office which amounted to 62 people and sampling was carried out based on the Krejcie table as many as 55 people. Data is presented through a frequency table and processed using score calculations. The data analysis technique uses a percentage formula. The results of this study show that the effectiveness of finger printing in the Soppeng Regency Environmental Office is carried out very well or very effectively. These results are seen from the aspects of: 1) achieving targets, namely achieving employee attendance and productivity with a percentage result of 92.25%, 2) employee adaptability to finger printing with a percentage result of 95.81%, (3) employee job satisfaction with a percentage result of 91.85%, (4) employee responsibility to complete work on time with a percentage result of 92%.